THE PLACE AND SIGNIFICANCE OF EDUCATION OF YOUNG CHILDREN THROUGH PHYSICAL EDUCATION - Xakimova Gulshan Abduxalilovna (Journals Park Publishing, 2024)
In this article, the author envisages covering the young generation with physical education, teaching and mastering it, and being able to apply the mastered movements in the activity, as well as the purposeful use of physical education tools.
Keywords: Physical education, tool, hygienic factor, healing power, efficiency, approach, communication, skill, quality, talent, talent.